FORMATION OF GENDER ROLES IN COMMUNICATIVE INTERACTION AND THEIR LINGUISTIC REPRESENTATION (International Conference on Education, Psychology and Humanities, 2026)
This thesis examines the formation of gender roles in communicative interaction and their representation through linguistic means. Gender roles are not only social and cultural constructs but also communicative phenomena that are constantly reproduced, negotiated, and transformed in speech. Language serves as one of the main instruments through which society assigns, maintains, and sometimes challenges gender-related expectations. The study focuses on how gender roles are formed in everyday communication, how they are reflected in lexical choices, speech strategies, discourse patterns, politeness formulas, metaphors, and pragmatic behavior. From a psycholinguistic and sociolinguistic perspective, gendered communication is interpreted as a dynamic process influenced by social norms, cultural values, cognitive stereotypes, and individual speech experience. The thesis argues that the linguistic representation of gender roles is not fixed; rather, it changes depending on social context, communicative purpose, status relations, and cultural environment.
Keywords: Gender roles, communicative interaction, linguistic representation, gender stereotypes, discourse, sociolinguistics, psycholinguistics, speech behavior.